Eph/Ephrin-mediated stimulation of human bone marrow mesenchymal stromal cells correlates with changes in cell adherence and increased cell death - Alfaro, David (Stem Cell Res Ther, 2018)
BACKGROUND: Mesenchymal stromal cells (MSC) are components of connective tissues and, in vitro, cell entities characterized by cell adhesion and immunophenotyping, although specific markers for their identification are lacking. Currently, MSC derived from either human bone marrow (BM-MSC) or adipose tissue (Ad-MSC) are considered the main sources of MSC for cell therapy. Eph receptors and their ligands, Ephrins, are molecules involved in cell adhesion and migration in several tissues and organs. In the current study, we analyze the pattern of Eph/Ephrin expression in MSC and evaluate the effects of blockade and stimulation of these receptor/ligand pairs on their biology. METHODS: Eph/Ephrin expression was analyzed in both BM-MSC and Ad-MSC by qRT-PCR. Then, we supplied BM-MSC cultures with either blocking or activating compounds to evaluate their effects on MSC proliferation, survival, and cell cycle by FACS. Changes in cytoskeleton and integrin α5β1 expression were studied in stimulated BM-MSC by immunofluorescence microscopy and FACS, respectively. RESULTS: Higher numbers of Eph/Ephrin transcripts occurred in BM-MSC than in Ad-MSC. In addition, the blocking of Eph/Ephrin signaling correlated with decreased numbers of BM-MSC due to increased proportions of apoptotic cells in the cultures but without variations in the cycling cells. Unexpectedly, activation of Eph/Ephrin signaling by clustered Eph/Ephrin fusion proteins also resulted in increased proportions of apoptotic MSC. In this case, MSC underwent important morphological changes, associated with altered cytoskeleton and integrin α5β1 expression, which did not occur under the blocking conditions. CONCLUSIONS: Taken together, these results suggest that Eph/Ephrin activation affects cell survival through alterations in cell attachment to culture plates, affecting the biology of BM-MSC. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13287-018-0912-3) contains supplementary material, which is available to authorized users.